Factors Affecting Minor Children Become Sex Workers In Kampung Kubur Kelurahan Petisah Tengah Sub-District Medan Petisah - Debby Rizki Ananda (IHSA Institute, 2020)
Prostitution of minors has been increasing concerned, a good number of cases of child exploitation on their children themselves or unknowingly already made public stunned. Indeed, anything can happen, especially in this modern era, everything can be done by anyone. Moreover, because the demands of the economy to the lack of supervision of a parent can make a child desperate to do something very dangerous. It is quite possible prostitution activities will be carried out by children under age. However, over the times, the most dominant factor of a child into prostitution is not poverty but a lifestyle demands.This research type of case studies, and analyzed using qualitative data analysis techniques. Based on research that has been conducted of the obtained factors influencing minors to sex work. As these factors are internal and external factors.Internal factors which affect minors into prostitution is a personality disorder, the effect of age, outlook or false beliefs and low religiosity. While external factors of a child into prostitution are economic factors, lifestyle, families who can not afford, environmental factors and peers.